Quality of Student Literature Critical Essay Writing In the Mimetic Perspective - Septyanti, Elvrin; Zulhafizh, Zulhafizh (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to determine the skills and quality of writing literary criticism essays of Study Program students of Indonesian Language and Literature education based on a mimetic approach. The method used is a qualitative method. The techniques used in this study are: (1) literature review, (2) observation, (3) documentation techniques, and (4) analytical techniques. The research data was obtained based on the students writing sheet about the literary criticism essay of the novel